Photodynamic therapy of deep tissue abscess cavities: Retrospective image‐based feasibility study using Monte Carlo simulation - Baran, Timothy M.; Choi, Hyun W.; Flakus, Mattison J.; Sharma, Ashwani K. (Medical physics (Lancaster), 2019)
Purpose Deep tissue abscesses remain a serious cause of morbidity, mortality, and hospital stay despite development of percutaneous drainage and increasing use of perioperative antibiotics. The goal of this study was to examine the feasibility of methylene blue (MB) mediated photodynamic therapy (PDT) for treatment of infected abscesses with intracavity MB delivery, using computed tomography (CT) imaging data from a representative abscess patient population and Monte Carlo simulation of light delivery. Methods This retrospective study included all adult subjects that received percutaneous abscess drainage between 1 January 2014 and 31 December 2014 at our institution whose abscess was confirmed by abdominal CT imaging less than 1 week preprocedure (n = 358). Of these, 40 subjects were further analyzed with Monte Carlo simulation. Abscess volumes were segmented from CT images, and imported into the Monte Carlo simulation space. Monte Carlo simulations were performed with a single fiber placement for each abscess, with the optical power at which a fluence rate of either 4 or 20 mW/cm2 was achieved for 95% of the abscess wall recorded. Subjects for which a fluence rate of 4 mW/cm2 was attainable in 95% of the abscess wall with a maximum input optical power of 2000 mW were considered eligible for MB‐PDT. Results 42.5% of subjects would have been eligible for MB‐PDT, with 17.5% attaining the higher threshold of 20 mW/cm2 in 95% of the abscess wall, given a 1% Intralipid concentration within the abscess cavity and the assumed abscess wall optical properties. The mean optical power necessary was 680 ± 580 mW for the 4 mW/cm2 threshold, and 1100 ± 600 mW for the 20 mW/cm2 threshold. Abscess surface area and threshold optical power were correlated (Spearman ρ = 0.73, P = 0.001), with larger abscesses requiring higher optical power. Of the subjects who were not eligible for MB‐PDT, abscess volumes (150 ± 120 vs 62 ± 41 cm3, P = 0.0049) and surface areas (320 ± 200 vs 140 ± 70 cm2, P = 0.0015) tended to be larger than for those who were eligible. There were no significant differences in eligibility, optical power required, or abscess volume or surface area based on abscess location. For all eligible subjects, at the optical power necessary to achieve 4 mW/cm2 in 95% of the abscess wall, 2.5 ± 3.7% (0%–13.2%) of the wall experienced a fluence rate greater than or equal to 400 mW/cm2. At the 20 mW/cm2 threshold, 8.8 ± 11.4% (0%–31.1%) of the wall surpassed this 400 mW/cm2 level. If subjects with greater than 5% of the wall exceeding 400 mW/cm2 are treated as ineligible, overall eligibility becomes 32.5% for the 4 mW/cm2 threshold and 10.0% for the 20 mW/cm2 threshold. Conclusions Assuming that the subjects analyzed were representative of the overall patient population, over 150 patients that received percutaneous abscess drainage during the study period would have been eligible for MB‐PDT at the time of drainage, with smaller abscesses being more amenable for treatment. This technique could potentially reduce abscess recurrence, duration of drainage catheter placement, and reliance on systemic antibiotics. These results motivate a future Phase 2 clinical trial following successful completion of the ongoing safety study.